Efektivitas Model Pembelajaran Berbasis Masalah terhadap Kemampuan Menulis Cerita Pendek pada Siswa SMA - Maula, Atiyatul; Khuzaemah, Emah; Herawati, Lilik (UNIB Press, 2024)
Short story writing skills are still difficult to master by high school students. One of the difficulties experienced by high school students is the difficulty in expressing ideas and interesting event sequences. Therefore, improvements are needed in the learning process of short story writing skills. One way to overcome students' difficulties in writing short stories is the application of problem-based learning (PBL) models. The study aims to determine how effective the problem-based learning model is on the short story writing skills of high school students. The population in this study were students of class XI of SMA Negeri 1 Astanajapura which consisted of 10 classes. The sample in this study was class XI MIPA 3 as the experimental class and class XI MIPA 4 as the control class, each of which consisted of 36 students. The data collection technique used the short story writing test technique. This study is a quantitative study with a quasi-experimental design. Based on the results of the study, it is known that the problem-based learning model is effective in the short story writing skills of high school students. This is indicated by the t-value of 0.000 <0.05, so the hypothesis is accepted. Then, the results of the data analysis also showed an increase in the results of the short story writing test in the control class and the experimental class, this was proven by the results of the pretest and posttest. In the control class consisting of 36 students, the pretest score was 55.58, and there was an increase in the posttest of 57.69. While in the experimental class consisting of 36 students, the pretest score was 61.19, and there was an increase in the posttest of 67.08. Although both experienced an increase, the results of the short story writing test in the experimental class experienced a greater increase than the control class.